Enhanced Cell Harvesting for Lipid Production by Lipomyces maratuensis InaCC Y720 Using Flocculation Induction - Kusumawati, Theresia; Kanti, Atit; Damayanti, Ema; Ilmi, Miftahul (Malaysian Applied Biology, 2025)
Lipomyces maratuensis InaCC Y720 is a yeast from Indonesia that is known to be able to produce lipids on a production medium that has been optimized in the previous study. One of the efforts to increase the harvesting of yeast cells needed on a production scale larger than the laboratory scale can be done by flocculation induction. This study showed that flocculation induction significantly increased the cell harvest of Lipomyces maratuensis InaCC Y720, with the biomass obtained increasing up to 2.7 times compared to the method without flocculation induction. The combination of pH 9 adjustment and the addition of Ca2+ ions proved to be the optimal conditions to induce flocculation, resulting in cell aggregations that appeared adherent based on scanning electron microscopy (SEM). These findings suggest that the flocculation induction not only improves cell harvesting efficiency but also has the potential to be applied in industrial-scale lipid production as a more effective harvesting method. Although the main composition of the fatty acids produced remained consistent, there were differences in the percentage of each fatty acid between harvesting methods with and without flocculation induction. However, to maximize the utilization of lipids from flocculated cells, further research is needed to develop more efficient extraction methods. Thus, this study provides a solid foundation for further exploration in the optimization of lipid production using oleaginous yeast.